The Activities of the 2nd and the 252nd Police Battalions Between 1941–1944 - Bubnys, Arūnas (Genocidas ir rezistencija, 2000)
The article analyses the activities of the 2 and 252 Lithuanian police battalions during the Nazi occupation. The history of the 2 is roughly divided into three periods. The first period covers July-November 1941; the second – November 1941, to November 1942; and the third one the period of 1943 to 1944. During its existence, the battalion for the most part was engaged in watching different military objectives (in 1941–1942 it guarded the Majdanek concentration camp), and in fights with Soviet partisans in East Lithuania, in Belarus (Svyriai county) and in Russia (Pskov region). However, during the first period of its existence, the unit was indirectly involved in some accomplishments of the Nazi holocaust plans. In 1941, it had twice convoyed Jews to the site of execution in Paneriai. Since the unit was not involved in big operations against partisans, its casualties in general were inconsiderable. The servicemen of the unit were loyal to civilians, and did not commit any war crimes against them.The fate of the unit was decided in a crucial encounter with the soviet armored troops during the last days of July 1944. The survivors of the battle either retreated to Germany, or hid in Lithuania.The 252 police battalion was formed in the autumn of 1942. The battalion could not have direct reference to the Nazi annihilation policy, since 80% of Lithuanian Jews had been liquidated late in 1941, and the rest in the period 1943–1944, were imprisoned in ghettos. During the service in Majdanek the unit watched the approaches to the camp and convoyed prisoners to work, and thus, did not participate in massacres. Like the 2 police battalion, the formation for the most part was engaged in watching different military objectives and fights with soviet partisans. The battalion was one of a few Lithuanian police battalions which, as an independent unit, existed as long as the autumn of 1944, and some of its officers continued their service until the end of the war.
Keywords: German occupation; police battalions; Holocaust